Nano Structured Bi2O3 Catalyzed Synthesis of 3-Phenyl-[1, 2, 4]Triazolo[3, 4-a]Phthalazines and Their Cross-coupling Reaction Under Aqueous Conditions. (7th February 2021) - Chacko, Priya; Shivashankar, Kalegowda
Abstract: A novel and an expeditious approach for the synthesis of 3-phenyl-[1, 2, 4]triazolo[3, 4- a ]phthalazine derivatives has been achieved from 1, 4-dichlorophthlazine and benzohydrazides in the presence of nano Bi2 O3 catalyst. 3-Phenyl-[1, 2, 4]triazolo[3, 4- a ]phthalazines undergo substitution reaction with various –OH group to produce 6-substituted-3-phenyl-[1, 2, 4]triazolo[3, 4- a ]phthalazines in excellent yields under aqueous condition in the presence of Pd(OAc)2, BINAP and nano Bi2 O3 catalyst. The present protocol tolerates various functional groups and represents a reliable and time efficient method. Graphical Abstract: